Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Une lutte sans trêve - Davis, Angela (La Fabrique, 2016)
Quels sont les liens entre l’industrie militaro-carcérale américaine, l’apartheid en Israël-Palestine, les mobilisations de Ferguson, Tahrir et Taksim ? Qu’est-ce que l’expérience des Black Panthers et du féminisme noir nous dit des rapports actuels entre les oppressions spécifiques et l’impérialisme ? Témoin et actrice de luttes de libération pendant plus d’un demi siècle, Angela Davis s’exprime ici sur l’articulation de ces différents combats, pour une nouvelle génération saisie par l’urgence de la solidarité internationale.
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; féminismes noirs; histoire et politique; intersectionnalité; inégalités; militance; pol4212; premier cycle; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Les femmes dans les professions scientifiques au Canada - Dionne-Simard, Dominique; Galarneau, Diane; LaRochelle-Côté, Sébastien (2016)
Le présent article fournit des renseignements sur les femmes âgées de 25 à 64 ans qui occupent des professions dans le domaine des sciences naturelles et appliquées (soit les professions scientifiques) au Canada, à l’aide des données des recensements de 1991 et 2001 et de l’Enquête nationale auprès des ménages (ENM) de 2011. Les conditions d’emploi des hommes et des femmes dans ces professions y sont également examinées au moyen de données provenant de l’Enquête sur la population active (EPA). • De 1991 à 2011, la part des femmes occupant une profession scientifique requérant des études universitaires est passée de 18 % à 23 %, et elle est passée de 14 % à 21 % dans les professions scientifiques de niveau collégial. • Au cours de la même période, la proportion de femmes est passée de 59 % à 65 % dans les professions non scientifiques de niveau universitaire, et de 41 % à 44 % dans les autres professions non scientifiques de niveau collégial. • Les femmes étaient à l’origine de 27 % de la croissance totale des effectifs dans les professions scientifiques de niveau universitaire observée de 1991 à 2011, mais de 75 % de la croissance des effectifs dans les professions non scientifiques de niveau universitaire. • Environ 60 % de la croissance des effectifs dans les professions scientifiques de niveau universitaire était attribuable au domaine de l’informatique. La contribution moindre des femmes à la croissance totale des effectifs dans les professions scientifiques est liée à leur faible représentation dans le secteur de l’informatique. • Les conditions d’emploi sont plus avantageuses pour les travailleurs occupant une profession scientifique. Toutefois, parmi ceux qui travaillaient à temps plein, les hommes gagnaient 9 % de plus que les femmes en moyenne, à la fois dans le secteur scientifique et le secteur non scientifique
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; femmes* scientifiques; inégalités; inégalités hommes-femmes; inégalités salariales; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Quelles politiques sexuelles pour les femmes noires ? - Hill Collins, Patricia; Marrec, Brigitte (Cahiers du Genre, 2016)
Partant du constat du silence des femmes noires sur leur sexualité, de l’invisibilité ou du traitement partiel de cet objet dans les recherches noires ou féministes en général, ce texte dresse le tableau des différentes approches possibles de la sexualité, celle des femmes noires en particulier. Si la sexualité peut se penser comme un système d’oppression autonome parallèle aux autres systèmes de race, de classe, de nation, de genre, on peut aussi la penser comme élément particulier de chaque système spécifique d’oppression. Mais l’analyse de la pornographie, de la prostitution, du viol invite plutôt à la penser comme ‘site d’intersectionnalité’ où se rencontrent et s’entrecroisent différents systèmes d’oppression.
Keywords: 1900-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; inégalités; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; soc1016; sociologie; système colonial; systèmes d'oppressions; thématiques; états-unis

Quand projet d’immigration rime avec inscription dans les cours de francisation. La trajectoire langagière de neuf immigrantes scolarisées dans la région montréalaise - Ralalatiana, Michela Claudie; Vatz-Laaroussi, Michèle (Diversité urbaine, 2016)
Pour les nouveaux arrivants, le fait d’apprendre la langue du pays d’accueil les aide dans leur processus d’intégration. C’est le cas des femmes immigrantes du Québec, bien que plusieurs autres défis les attendent. Malgré tout, elles sont travaillantes et motivées dans cet apprentissage. Cet article présente une recherche portant sur la trajectoire langagière de neuf femmes immigrantes inscrites dans un programme de francisation au Québec. Par la démarche de la biographie langagière, des entrevues semi-dirigées et un journal d’apprentissage tenu durant quatre mois, ces neuf femmes scolarisées et inscrites à des cours de français à temps complet ont été interrogées sur leurs contacts avec la langue française, les langues parlées en classe au Québec et à la maison, leurs réseaux d’amis et leurs activités sociales. Globalement, elles sont proactives, s’ajustent au lieu où elles se trouvent, à l’Autre et aux enjeux du moment.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; inégalités; justice sociale; montréal; outils; pour des recherches en milieux de pratiques; premier cycle; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; soc1061; sociologie; systèmes d'oppressions; thématiques; travail